Group maturity, team efficiency, and team effectiveness in software development: A case study in a CMMI‐DEV Level 5 organization. Issue 4 (21st October 2019) - Ramírez‐Mora, Sandra L.; Oktaba, Hanna; Patlán Pérez, Juana
Abstract: Group aspects are essential to the success of software projects; however, almost no research regarding group maturity in CMMI‐DEV Level 5 organizations has been conducted. The objective of this work is to investigate group maturity and its relationship to the efficiency and effectiveness of Agile Software Development teams in a CMMI‐DEV Level 5 organization. A case study was conducted, and three data collection methods were used: a validated questionnaire was given to nine agile software teams (59 people) to measure specific aspects of group maturity, team efficiency, and team effectiveness; the effort to develop Use Case Points and a group rate (related to productivity and salary) were collected to investigate team efficiency, and focus group sessions and semi‐structured interviews were conducted with project managers and team leaders to explore group issues in software development. Aspects of group maturity were correlated with team effectiveness and team efficiency measures. Communication was found to be strongly correlated with team effectiveness and group rate, and conformity and the clarity of roles and goals were found to be strongly correlated with team efficiency. The results suggest that group maturity has a positive influence on software teams in CMMI‐DEV Level 5 organizations. Abstract : A case study was conducted in a CMMI‐DEV Level 5 organization to investigate the way in which group maturity was related to the efficiency and effectiveness in software development. Communication was found to be strongly correlated with team effectiveness, and conformity and the clarity of roles and goals were found to be strongly correlated with team efficiency. The results suggest that group maturity has a positive influence on software teams in CMMI‐DEV Level 5 organizations.